Estimativa do saldo de radiação em cultivo irrigado de cana-de-açúcar utilizando dados de sensoriamento remoto orbital - Sá, Pâmella Crisley Costa de (Universidade Federal Rural do Semi-Árido, 2016)
In Brazil there is a great irregularity and no radiation data that has just committing several studies. Thus, the use of remote sensing techniques is presented as a promising field, with the advantage of determining the components of the radiation balance with high spatial coverage quickly and accurately, and together with surface data have been indispensable in the application models and algorithms to estimate the components of the energy balance at the surface and evapotranspiration at various scales of time and space, which is the main factor to be considered in estimating water needs of the crop. The aim of this research project was to determine the components of the radiation balance in sugarcane area from MODIS (MODIS) inserted in SEBAL model (Surface Energy Balance Algorithm for Land) and validate them with data to the surface in the production area of sugarcane irrigated belonging to the company Agribusiness of the São Francisco Valley SA - Agrovale in Juazeiro - BA. It was concluded that there was no unusual condition in the behavior of the terms of the radiation balance obtained on the surface, when considering the different growth stages although the absolute values of the terms were different. The terms of the Radiation Balance found through MODIS images by applying the model SEBAL had expected behavior for targets with consistent and similar values to those found on the surface except for the albedo that had errors 54.5%, 50%, 11.7% and 26% for phases I to IV, respectively. Finally, the evapotranspiration using Rn from the satellite imaging showed no significant difference we react to ETcBERB and ETcPM1. It follows, therefore, that remote sensing can be perfectly used in determining the water needs of the crop of sugarcane in the region under study
Keywords: Fluxo radiativo; Evapotranspiração; Saldo de radiação.; Radiative flux; Evapotranspiration; MODIS; SEBAL; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO